Computer testing of effectiveness of using glass-fibre-reinforced-polymer in design of running limbs type Cheetah Foot (Damascus University Journal for engineering sciences, 2022)
Traditional prosthetics provide constant or controlled speeds for amputees, but due to the presence of a large group of young people and amputees, especially in developing countries and countries of war, and in order to preserve their mental health and physical fitness, our interest was to make the amputees able to jump and run for great distances and closer to normal through using a prosthesis with an appropriate design in terms of weight, durability and cost, which is the main objective of this research. Cheetah feet prosthetic are usually designed from carbon fiber reinforced polymer, which is known for its great ability to bear the periodic weights applied to it, but due to its complex manufacturing process and high price, which is reflected in the price of the entire limb, we worked in this study to test the possibility of designing the limb from other materials that are less expensive and less complex. In the process of manufacturing it, and at the same time, it has a high strength and low weight in comparison to carbon fibers, which is a glass fiber reinforced polymer (GFRP). We designed a numerical model of a Cheetah foot prosthetic using SOLIDWORKS 2016 x64 Edition for an amputee of mass 70 kg, length of 190 cm, and a 24-year-old who was subjected to a unilateral lower knee amputation. Then, we transformed the model into a mesh of finite elements then after ensuring the quality of the mesh and the validity of the numerical model. We tested it with two types of tests, the first one determines how much weight can it withstand before it collapses using static analysis, the second test is the fatigue test by which we can determine the life span of the designed prosthesis. We found that by using S2 glass fiber material with epoxy polymer it is possible to obtain a running prosthesis that is lightweight, has high strength, is affordable and has a good lifespan.
Keywords: GFRP; CFRP; S2-glass-fiber; epoxy; SOLIDWORKS; FEM; cheetah foot; prosthesis